2019
DOI: 10.21873/invivo.11735
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Endocrine Disorders in Childhood Brain Tumor Survivors in South Korea

Abstract: Background/Aim: This longitudinal study aimed to analyze the prevalence of endocrine disorders in childhood brain tumor survivors in South Korea using claims data. Patients and Methods: We identified in 1,058 patients from a nationwide cohort of patients diagnosed with brain tumors between January 1st 2009 to March 29th 2016. Multivariable logistic regression was used to evaluate associations between clinical factors and endocrine disorders. Results: After a median follow-up of 60.0 months, 393 (37.1%) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…[6][7][8][9][10] The median time to endocrinopathy onset was 2 years from the initial diagnosis. Similarly, studies by Clement et al 8 and Heo et al 10 indicate that most endocrine disorders appeared at a median time of 2.2 years after the initial diagnosis. Hence, treating oncologists should be vigilant about endocrine screening in this subset of patients to ensure early referral to endocrinologists for optimal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] The median time to endocrinopathy onset was 2 years from the initial diagnosis. Similarly, studies by Clement et al 8 and Heo et al 10 indicate that most endocrine disorders appeared at a median time of 2.2 years after the initial diagnosis. Hence, treating oncologists should be vigilant about endocrine screening in this subset of patients to ensure early referral to endocrinologists for optimal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the duration of follow-up from the initial diagnosis may have been too brief, as several studies have suggested that endocrine disorder can occur up to 20 years following initial diagnosis of malignancy. 10…”
Section: Discussionmentioning
confidence: 99%
“…Those diagnosed with any form of cancer between 2008 and 2009 were excluded. The patients who did not require oncology treatment for any type of cancer during the 2year (washout) period starting in 2008 were considered cancer-free [8]. We included patients having cancer associated with good prognoses, such as breast (C50), stomach (C16), colorectal (C18-20), and prostate cancer (C61), classified according to the International Classification of Diseases (ICD) 10th Revision.…”
Section: Methodsmentioning
confidence: 99%
“…The patients who did not require oncology treatment for any type of cancer during the 2-year (washout) period starting in 2008 were considered cancer-free [8]. We included patients having cancer associated with good prognoses, such as breast (C50), stomach (C16), colorectal (C18-20), and prostate cancer (C61), classi ed according to the International Classi cation of Diseases (ICD) 10th Revision.…”
Section: Methodsmentioning
confidence: 99%